2021
DOI: 10.1088/2051-672x/ac2a0f
|View full text |Cite
|
Sign up to set email alerts
|

Tribological characteristics of mahua oil with graphene nanoplatelets as anti-wear and extreme pressure additive

Abstract: The tribological investigation was performed to seek the role of graphene nanoplatelets (GNPs) in enhancing the physico-tribological properties of mahua oil. The flashpoint, fire point, viscosity, wear preventive characteristics (WPC) and extreme pressure characteristics (EPC) were conducted following the governing standards. A substantial decrement of 17% in the coefficient of friction, 15.15% in wear scar diameter was observed upon blending the 0.25 wt.% GNPs with mahua oil. The WPC morphology on the steel b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Zinc oxide was blended with mahua oil in the concentrations 0.25 wt.% (0.25MO), 0.5 wt.% (0.5MO), 0.75 wt.% (0.75MO), and 1 wt.% (1MO) [11][12][13]. Out of the various methods for dispersion, the authors found that ultrasonication was the most efficient technique [14][15][16], wherein sound energy is applied to agitate the particles. It generates alternating low pressure and highpressure waves which helps in uniform distribution of Nano-additives in the base oil.…”
Section: Mahua Oil Preparationmentioning
confidence: 99%
“…Zinc oxide was blended with mahua oil in the concentrations 0.25 wt.% (0.25MO), 0.5 wt.% (0.5MO), 0.75 wt.% (0.75MO), and 1 wt.% (1MO) [11][12][13]. Out of the various methods for dispersion, the authors found that ultrasonication was the most efficient technique [14][15][16], wherein sound energy is applied to agitate the particles. It generates alternating low pressure and highpressure waves which helps in uniform distribution of Nano-additives in the base oil.…”
Section: Mahua Oil Preparationmentioning
confidence: 99%
“…As part of the Taguchi method, the following steps are performed: selection of an appropriate orthogonal matrix, identification of factors and interactions, transferring those factors and interactions to columns of orthogonal matrices, conducting experiments, analyzing the dataoptimal levels must be determined and all these steps must be verified. A, B, and C represent the three input control factor parameters (Pulse Energy, Number of Spots, and Diameter of Spot, respectively), and their levels in table 4. In equation (4), since the number of levels (L) and numbers of factors (f) are both 3, the degree of freedom (DOF) can be calculated:…”
Section: Surface Profilingmentioning
confidence: 99%
“…Therefore, they are widely used for automotive, aerospace, construction industries, and marine applications [1][2][3]. Aluminum 7075 alloy is age-hardened among all other aluminum alloys; hence, comparatively, it possesses higher strength [4,5]. AA7075 T651 is of high strength in combination with low density (2810 kg m −3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nano-additives enhance the lubricant's thermo-physical properties. The studies [10][11][12][13][14][15][16][17][18][19][20][21][22] show that nano-particles are effective EP additives.…”
Section: Introductionmentioning
confidence: 99%